1995
DOI: 10.1080/15287399509532039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone on the epithelial and inflammatory responses in the airways: Role of tumor necrosis factor

Abstract: We have investigated the possibility that tumor necrosis factor alpha (TNF) plays a role in the increased airway permeability and an inflammatory response following an acute ozone (O3) exposure. Male Sprague-Dawley rats were injected, intraperitoneally, with either rabbit anti-mouse antibody to TNF (anti-TNF) or preimmune rabbit serum, 2 h before a 3-h exposure to O3 or purified air. Permeability, as determined by [99mTc] diethylenetriamine pentaacetate (DTPA) transport, total protein and albumin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Although TNF-α is chemotactic for neutrophils and enhance the movement of inflammatory cells (27), ozone-induced neutrophil migration was not affected in p55/p75 TNF-receptor knockout mice following a 2ppm exposure for 3 hours, but ozone-induced AHR was reduced (28), implicating a non-neutrophilic TNF-α dependent AHR. Furthermore, ozone-induced changes in tracheal permeability which may contribute to airway wall oedeama and may also facilitate the recruitment of inflammatory cells into BALF and tissues (9) are inhibited by an anti-TNF-α blocking antibody (29). Taken together, our data confirm previouslypublished data and support in part the premise that IL-6 is primarily involved in…”
Section: Discussionsupporting
confidence: 89%
“…Although TNF-α is chemotactic for neutrophils and enhance the movement of inflammatory cells (27), ozone-induced neutrophil migration was not affected in p55/p75 TNF-receptor knockout mice following a 2ppm exposure for 3 hours, but ozone-induced AHR was reduced (28), implicating a non-neutrophilic TNF-α dependent AHR. Furthermore, ozone-induced changes in tracheal permeability which may contribute to airway wall oedeama and may also facilitate the recruitment of inflammatory cells into BALF and tissues (9) are inhibited by an anti-TNF-α blocking antibody (29). Taken together, our data confirm previouslypublished data and support in part the premise that IL-6 is primarily involved in…”
Section: Discussionsupporting
confidence: 89%
“…Our findings that mice lacking TNFα are protected from ozone-induced injury are consistent with this idea. A similar protective effect against ozone-induced injury has been reported in TNFR1 and/or TNFR2 knockout mice Shore et al, 2001;Cho et al, 2007), and in mice pretreated with anti-TNFα antibodies (Piguet and Vesin, 1994;Young and Bhalla, 1995;Kleeberger et al, 1997;Cho et al, 2001;Bhalla et al, 2002).…”
Section: Discussionsupporting
confidence: 75%
“…This is supported by findings that administration of antibodies to TNFα attenuates ozone-induced increases in macrophage adherence, neutrophil accumulation and IL-1 and IL-6 expression in the lung, and that ozone-induced inflammation and macrophage activation are reduced in TNFR1 knockout mice (Young and Bhalla, 1995;Kleeberger et al, 1997;Pearson and Bhalla, 1997;Cho et al, 2001;Bhalla et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…In support of this hypothesis, we and others have demonstrated that lack of TNF response provided significant protection from O 3 -induced inflammation and airway hyperreactivity in rodent lungs (16)(17)(18)(19)(20). Moreover, recent studies (21,22) demonstrated in human subjects an association of O 3 -induced lung functional changes with a TNF polymorphism haplotype including -308A, which is also known to be involved in increased risk of asthma (23).…”
mentioning
confidence: 63%
“…inflammation, hyperpermeability, and cell proliferation after acute or subacute O 3 exposure in rodents (17,19,20,36). Lung inflammation and epithelial injury were also reduced after subacute O 3 exposure in mice genetically deficient in TNF-R (Tnfr1…”
Section: Discussionmentioning
confidence: 92%